Effects of Ethanolic Extracts of Fruits of Acacia nilotica and Flowers of Calotropis procera on Liver Function of Aspirin-Induced Male Albino Rats - Ismail, Muhammad Zuhairah; Chinedu, Imo; Adebisi, Arowora Kayode; Philip, Shadrach; Mohammed, Rashida Ismail; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
This study examined the effects of ethanolic extracts of fruits of Acacia nilotica and flowers of Calotropis procera on the liver function of male albino rats. Acacia nilotica fruits and Calotropis procera flowers are commonly consumed by natives in northern Nigeria for therapeutic purposes. Eighty-four (84) healthy male albino rats were used for this study. The animals were randomly distributed into six groups of ten animals each, while 24 rats were used for lethal dose (LD50) analysis. The animals were administered ethanolic extracts of fruits of Acacia nilotica and flowers of Calotropis procera for 5 and 14 days respectively after induction with aspirin. The study was carried out in two phases: The animals were induced with 500 mg/kg body weight of aspirin 12 hours before the commencement of the experiment, the test animals were administered ethanolic extract of fruit of Acacia nilotica and flowers of Calotropis procera for 5 and 14 days and sacrificed at the end of each test phase respectively, blood was collected for biochemical analysis. The liver was harvested at the end of each phase, processed for histological investigation and photomicrographs taken. The result of liver function parameters showed that the mean values of alanine transaminase (ALT) after five-day of treatment decreased non-significantly (p>0.05) in groups 4, 5 and 6 and decreased significantly (p<0.05) in group 4 when compared to normal control. Also, ALT increased significantly (p<0.05) in group 2. There was a general decreasing trend in the mean values of aspartate transaminase (AST) across all groups except group 2. The mean values of alkaline phosphatase (ALP) decreased significantly (p<0.05) in all groups, but increased non-significantly in group 2. The same trend was observed in the values of ALT, AST, and ALP after 14 days of treatment. Photomicrograph of the liver section of normal rats showed normal central vein, sinusoids and hepatocytes as well as that of the treated animals. Photomicrograph of liver section of rat administered aspirin only showed slightly dilated portal triad after five days. The study suggests that the ethanolic extracts from fruits of Acacia nilotica and flowers of Calotropis procera may have active ingredients that are capable of improving some liver functions.